Rekonstruksi Etika Keguruan dalam Ekosistem Literasi Digital: Studi Fenomenologis tentang Praktik Profesional Guru Indonesia - Ahmad Muflihul Fakih; Imron Fauzi (Mathematics Education Study Program, 2025)
This study examines how teachers reinterpret teaching ethics in the context of digital literacy-based education, addressing the gaps in previous studies that primarily viewed digital literacy as a technical skill. Using a qualitative phenomenological design, the study involved 80 purposively selected teachers who participated in digital learning practices. Data were collected through in-depth interviews, observations, and documentation, then analyzed using thematic coding, with stages of data reduction, data presentation, and conclusion drawing. The results show that digital literacy is understood not only as a technological skill but also as an ethical foundation inherent in teachers' professional judgment. Five main themes emerged: ethical awareness shaped by digital literacy, critical reflection on technology use, the construction of contextual ethical norms, the role of teachers as role models of digital ethics, and the need for institutional strengthening. Challenges faced include limited access to digital resources and a lack of digital ethics training. This study offers a novel theoretical contribution by integrating digital literacy as a contextual variable within the framework of teacher professional ethics, while also providing practical implications for policy development and teacher training in responding to ethical demands in the digital education era.